2014
DOI: 10.1093/ndt/gfu234
|View full text |Cite
|
Sign up to set email alerts
|

The urinary proteome as correlate and predictor of renal function in a population study

Abstract: The urinary proteome refines the diagnosis of existing or progressing renal dysfunction and predicts cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 27 publications
2
70
0
Order By: Relevance
“…105 In a cohort of 797 randomly selected individuals, the CKD273 score was significantly predictive of a decline in renal func tion over 4.8 years of followup, further confirming the effectiveness of this urinary proteomebased classifier. 104 These findings also demonstrate the value and consist ency of urinary levels of collagen fragments as proteomic biomarkers. A substantial decrease in urinary levels of collagen fragments is, evidently, a common feature of many forms of renal dysfunction, including diabetic nephropathy 98,100,103,106,109,110 and CKD.…”
Section: Insights From Early Proteomic Studiesmentioning
confidence: 65%
See 1 more Smart Citation
“…105 In a cohort of 797 randomly selected individuals, the CKD273 score was significantly predictive of a decline in renal func tion over 4.8 years of followup, further confirming the effectiveness of this urinary proteomebased classifier. 104 These findings also demonstrate the value and consist ency of urinary levels of collagen fragments as proteomic biomarkers. A substantial decrease in urinary levels of collagen fragments is, evidently, a common feature of many forms of renal dysfunction, including diabetic nephropathy 98,100,103,106,109,110 and CKD.…”
Section: Insights From Early Proteomic Studiesmentioning
confidence: 65%
“…[98][99][100][101] Subsequent studies assessed the prognostic value of various urinary proteins for development of macro albuminuria, worsening of albuminuria, progression towards ESRD or death. 98,[102][103][104][105][106] An analysis of the urinary peptidome of 21 patients with type 1 diabetes mellitus showed that a significant decrease in fragments of collagen α1 (IV) chain, col lagen α1 (V) chain and tenascin X, and an increase in fragments of inositolpentakisphosphate 2 kinase, tight junction protein zona occludens 3 and protocadherin fat 2 (also known as FAT tumour suppressor 2) was associated with an early decline in renal function. 98 In another study, a reduction in urinary collagen α1 (I) chain fragments in patients with type 1 diabetes was predictive of increased albuminuria.…”
Section: Insights From Early Proteomic Studiesmentioning
confidence: 99%
“…[6][7][8] Further prospective studies should underpin its use in clinical practice compared with other biomarkers over varying intervals of follow-up in relation to different end points. A previous publication in the same cohort demonstrated that the early diastolic peak velocity of the mitral annulus (e′) predicts the incidence of fatal combined with nonfatal cardiovascular events over a 5-year follow-up period.…”
Section: Perspectivesmentioning
confidence: 99%
“…7 A study in the same population revealed that the urinary proteome predicted progression of chronic kidney disease from grade 2 or lower to stage 3 or higher. 8 In the light of our previous observations, [6][7][8] we investigated in a random population sample whether the urinary proteome predicts cardiovascular events over and beyond traditional risk factors.…”
mentioning
confidence: 99%
“…Broad evidence has been presented in the literature for a convincing diagnostic and prognostic performance of a multiparametric urinary peptide panel termed CKD273 (Argiles et al, 2013;Siwy et al, 2014;Gu et al, 2014;Critselis & Lambers Heerspink, 2015;Schanstra & Mischak, 2015).…”
Section: Biomarker Discovery In Ckdmentioning
confidence: 99%